Light and scanning electron microscopy of the tongue of the sand lizard (Lacerta agilis) - Cizek, P; Hamouzova, P; Kvapil, P; Kyllar, M (Folia morphologica, 2019)
BACKGROUND: Despite the fact that numerous reptile species are widely studied by the researchers, information describing the detailed structure of particular organs in many reptiles is missing. MATERIALS AND METHODS: The tongue of the sand lizard (Lacerta agilis) was examined under the light and scanning electron microscope. It is divided into bifurcated apex, corpus and bifurcated radix. The tip of the lingual apex is devoid of lingual papillae. RESULTS: The remaining dorsal surface of the tongue bears either fused papillae in the form of caudally directed ridges or individual papillae represented by mu- shroom-like or semilunar prominences (lingual apex) or fish scale-like papillae (lingual corpus) and horizontally laid ridges extending in the form of lobulated prominences (lingual corpus, lingual radix). Regardless of the shape, lingual papillae contain numerous muscle fibres and they are all considered to be mechanical. The lingual epithelium changes from the simple squamous into stratified squamous in the caudal direction. No salivary glands or sensory structures were recognised. CONCLUSIONS: This description is to be used mainly for comparative studies. It could also help to understand how different lizards capture the pray.
Keywords: ještěři; Animals; mikroskopie elektronová rastrovací; Tongue; Microscopy, Electron, Scanning; Lizards; zvířata; jazyk